Digitalization in the Community-based Tourism Development in Peripheral Areas: A Case Study of Sumbermanjing Wetan Village, Malang Regency - Rini, Ayu Dwidyah (JAS (Journal of ASEAN Studies), 2019)
The paradigm of digital-based peripheral area tourism development is carried out within a broader development of technology and communication in Indonesia. This is done as a way to reduce the level of disparity between the city and the peripheral region. This study examines the paradigm of local communities related to digital-based tourism development. This digital-based tourism development is illustrated through the case of community-based tourism in the Sumbermanjing Wetan area of Malang Regency. This article shows that community participation in tourism is classified into three forms of local participation. First, digital-based tourism can be solutions for tourism development in the Sumbermanjing Wetan region. Second, the community also understand the digitalization of tourism as an effort to alleviate poverty and improve the welfare of local communities. Third, digital-based tourism can be the strategy for improving the quality of life of the Sumbermanjing Wetan community.